Prospek Pemanfaatan Limbah Pertanian Sebagai Pupuk Organik Cair (POC) Pada Budidaya Tanaman Sawi (Brassica juncea L.) Dalam Pot - Robiatul Adawiyah; Terry Pakki; Namriah Namriah; Agung Yuswana (University of Halu Oleo, 2022)
This study aims to determine the prospects for utilization of agricultural waste in the cultivation of mustard greens (Brassica juncea L.) in pots. This research was conducted in the Padaleu Village, Kambu District, Kendari City and the Laboratory ofthe Agronomy Unit of the Faculty of Agriculture, Halu Oleo University. The research was carried out from September to November 2018. The design used in this study was a one-factor randomized block design (RDB), namely the type of liquid organic fertilizer (LOF) various agricultural wastes consisting of control (P0), LOF of jackfruit waste (P1), LOF of banana weevil (P2),and LOF of Moringaleaves (P3).The LOF was given with the same concentration, namely15ml L-1 of water. Each treatment was repeated 3 times in order to obtain 12 experimental units and each experimental unit consistedof 3 plants for a total of 36 plants. The variables observed were plant height (cm), number of leaves (strands), leaf length (cm), leaf width (cm), wet weigh tand dry weight of mustard plant stover (g), wet weight and dry weight of mustard roots (g). There sults showed that the LOF treatment of various types of agricultural waste had a significant effect on all the observed variables. The effect of jackfruit waste LOF, banana weevil LOF and Moringa leaf LOF was the same effective for all observed variables, but significantly different from treatment without LOF (control). Therefore, the three typesof LOF are very prospective to be used as LOF to reduce the use of inorganicfertilizers. Key words: Agricultural waste, mustard greens, liquid organic fertilizer. Abstrak Penelitian ini bertujuan untuk mengetahui prospek pemanfaatan limbah pertanian pada budidaya tanaman sawi (Brassica juncea L.) dalam pot. Penelitian ini dilaksanakan d iKelurahan Padaleu Kecamatan Kambu Kota Kendari dan Laboratorium Unit Agronomi Fakultas Pertanian Universitas Halu Oleo. Pelaksanaan penelitian berlangsung dari Bulan September sampai Bulan November 2018. Rancangan yang digunakan dalam penelitian ini adalah rancangan acak kelompok(RAK) satu faktor yaitu jenis pupuk organik cair (POC) berbagai limbah pertanian terdiri atas control (P0), POC limbah nangka (P1), POC bonggol pisang (P2),dan POC daun kelor (P3). Pemberian POC tersebut dengan konsentrasi yang sama yaitu 15 ml L-1 air. Setiap perlakuan diulang 3 kali sehingga diperoleh 12 unit percobaan dan setiap unit percobaan terdiri dari 3 tanaman sehingga total 36 tanaman. Variabel yang diamati yaitu tinggi tanaman (cm), jumlah daun (helai),panjang daun (cm),lebar daun (cm), bobot basah dan bobot kering brangkasan tanaman sawi (g), bobot basah dan bobot kering akar tanaman sawi (g). Hasil penelitian menunjukkan bahwa perlakuan POC berbagai jenis limbah pertanian berpengaruh nyata terhadap semua variable lpengamatan. Pengaruh pemberian antara POC limbah nangka, POC bonggol pisang dan POC daun kelor sama terhadap semua variabel pengamatan, namun berbeda nyata dengan perlakuan tanpa POC (kontrol). Oleh karena itu ketiga jenis POC tersebut sangat prospek dijadikan sebagai POC untuk mengurangi penggunaan pupuk anorganik. Kata kunci: Limbah pertanian,tanaman sawi, pupuk organik cair.